Connectivity analysis of passive cluster with high stability in vehicular wireless network - Gong-an QIU; Zhi-hua BAO; Guo-an ZHANG; Shi-bing ZHANG (Tongxin xuebao)
A passive cluster model with the maximum lifetime was proposed for vehicle to vehicle communication based on the relative velocity. The cluster head was elected based on the average relative velocity and the neighbor list. The cluster lifetime was deduced as the function of the average relative velocity. The traffic safety messages were dissemi-nated to all cluster members by inter-cluster message broadcasting and intra-cluster message relaying in interconnected vehicular network. The link connectivity probability between the cluster head and members were deduced as the function of the vehicle density for inter-cluster broadcasting. The path connectivity probability between the cluster head and the neighbor cluster head was deduced as the function of the vehicle density and intra-cluster distance for on intra-cluster dis-semination. Simulation results show that the connected probability is suitable for vehicular network under the traffic den-sity constraints.